The impact of the COVID-19 pandemic on nursing care and nurses' work in a neonatal intensive care unit - Simsek, Didem Coskun; Gunay, Ulviye; Ozarslan, Suemeyye (Elsevier Science Inc, 2022)
Purpose: This study was conducted to determine the effects of the COVID-19 pandemic process on nursing care and nurses' work in neonatal intensive care units. Design and methods: The study was conducted using a qualitative method. The data were collected by voice recording with a one-on-one in-depth interview technique, and a semi-structured question form was used in the interviews. The data obtained from voice recordings were evaluated using the qualitative content analysis method. Results: The main themes and subthemes of the study were as follows: (1) decrease in physical contact with newborns due to fear of transmitting Covid-19 (decrease in physical contact between neonatal nurses and newborns, decrease in physical contact between mothers and newborns, decrease in physical contact between fathers and newborns), (2) communication problems between healthcare professionals and parents (3) changes in the working conditions for neonatal nurses (increase in the frequency and duration of work intense working speed, exhaustion and decreased motivation due to use of protective equipment). Conclusion: The COVID-19 pandemic process led to a decrease in nurses' and parents' touching newborns, nurses' experiencing problems with parents due to measures taken, heavier working conditions and a decrease in motivation for nurses. Practice implications: This study will inform future research to be directed to nursing care and the work of nursing who work on the front line in the COVID-19 pandemic process. (c) 2022 Published by Elsevier Inc.
Keywords: COVID-19 pandemic; Newborn; Neonatal nurse; Neonatal care; Parents